Synthesis and Characterization of Polymeric Nanoparticles and Capsules as Payload for Anticancer Drugs and Nanomedicines. (2016) - Amgoth, Chander; Dharmapuri, Gangappa
Abstract: Novel and bio-compatible polymeric nano scale cuboid particles and spherical nanoporous capsules have been developed by the synthesis of AB-type block copolymer from L-Alanine (L-Ala) and polycaprolactone (PCL). The morphology of (L-Ala)-b-(PCL) particles depends on dispersion solvents. Block copolymer (BCP) gives spherical nanoporous capsules upon dispersion in ethanol and cuboid particles in water. Herein, we have engineered nano (∼200 nm) scale polymer (cubic and spherical shaped) capsules for enhanced anticancer drug (Imatinib-ITM) loading and controlled and sustained release for therapeutics in cancer therapy. Synthesis of BCP followed without using any surfactants and precursors. The formation of cubic and spherical polymeric capsules is associated with the self-assembly of (L-Ala)-b-(PCL) due to presence of active functional groups. Spherical nanoporous capsules have been used to develop nanoformulations to kill the cancerous (K562-leukemia blood cancer) cells. These nanoformulations played a key and potential role to load nanomedicine to check the cancer cell inhibition and rupture upon incubation for 24 h in CO2 incubator.